Comparison of Acute Physiology and Chronic Health Evaluation II and Sequential Organ Failure Assessment intensive care unit scoring system as mortality predictors in intensive care unit patients with sepsis - Lokesh SB,; Latha V, (Asian Journal of Medical Sciences, 2024)
Background: Sepsis is a life-threatening organ dysfunction caused by a deregulated host response to infection. It is one of the leading causes of in-hospital mortality and morbidity among patients. It also results in significant morbidity and financial burden. Aims and Objectives: (1) To study the etiological profile of patients admitting with sepsis to ICU. (2) To compare between APACHE II and SOFA ICU scoring system of patients with sepsis at admission and at 24 h in predicting the 5th-day mortality. Materials and Methods: This was a single center hospital based prospective, observational, study conducted in patients in ICUs of ESICMC PGIMSR and Model Hospital Rajajinagar, Bangalore. Patients over age 18 years admitted in ICU who have fulfilled the criteria for sepsis were included in our study. Their clinical profile, APACHE II and SOFA scores were evaluated and followed up to 5th day of admission and data were compared with respect to patients’ outcome in the form of survival. Results: In this study, out of 53 patients the maximum number of patients belong to the age groups of >60 years (23 patients). Male-to-female distribution in this study noted was 30 and 23 patients, respectively. Aspiration Pneumonitis (17%) and Community-Acquired Pneumonia (17%) were the most common causes of septic. Out of 53 patients, 31 patients did not survive. In this study, it was observed that the SOFA scoring had the highest specificity (87.10%) and APACHE II had the highest sensitivity (96.77%) at admission. However at 24 h of admission, both the highest sensitivity and highest specificity was more for APACHE II score. The most area under the Receiver-operating characteristic curve was better for SOFA score (AUROC=58.0%) at admission than APACHE II score with AUROC of 53.7%, however AUROC of both SOFA and APACHE II score calculated at 24 h of admission were equally good in predicting 5th-day mortality. Conclusion: We found that the SOFA score outperformed APACHE II scores in predicting survival in septic shock patients at admission. SOFA and APACHE II calculated at 24 h of admission and both scores provided equal efficacy in predicting 5th-day mortality in patients with sepsis.